Overview of the Lunch Menu in the Play Group (KB) of Darul Hikam Kindergarten, Cirebon City - Amelia, Aam; Kunaepah, Uun; Adiyaksa, Jongga (Jurnal Medisci, 2025)
Background. A full-day school is an educational system whose learning runs from morning to evening, or over one day. In Indonesia, schools that implement the lunch program are still relatively few, accounting for 0.16% in 2016. School feeding is enforced to meet students' macro- and micronutrient needs, so that later it can improve students' intake and nutritional status. However, implementing the school lunch program faces several obstacles. This is due to the poor quality of the menu and the lack of variety, so students do not have the opportunity to choose their food. Play Group (Kb), Tk Darul Hikam Cirebon, is one of the full-day schools that provides lunch. Aims. The purpose of this study is to find out the description of the lunch menu in the Play Group (Kb) of Tk Darul Hikam Cirebon. Methods. This study uses Descriptive Observational. The data collected are both primary and secondary. Primary data includes setting menu patterns, portion standards, menu cycles, and menu arrangement using Checklist Sheets. Secondary data on the general picture in the Play Group (KB) at Darul Hikam Kindergarten in Cirebon City were obtained from the principal. Result. The research results of the Play Group (KB) at Darul Hikam Cirebon Kindergarten have established a menu pattern comprising carbohydrate dishes, animal side dishes, navati side dishes, and fruits. The Play Group (KB) of Darul Hikam Cirebon Kindergarten does not have a standard portion except for animal side dishes and selinagan. The menu cycle is 5 days, and the lunch menu is arranged in accordance with the principles of balanced nutrition. Conclusions. The Play Group (KB) of Darul Hikam Cirebon Kindergarten does not have a standard portion except for animal side dishes and selinagan Involvement. The menu cycle is 5 days, and the lunch menu is arranged in accordance with the principles of balanced nutrition.